2004
DOI: 10.1002/hlca.200490161
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Synthesis of Di‐ and Trisaccharide Analogues of Moenomycin A. Modifications in Unit E and in the Lipid Part

Abstract: Routes allowing the synthesis of moenomycin analogues with one modified sugar component and with new lipid parts were developed (see 10c, 12c, 16b, and 20b in Schemes 2 ± 4). It is anticipated that such analogues will be useful for studying the mode of action of the moenomycin-type transglycosylase inhibitors in detail and for preparing analogues with improved pharmacokinetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Unlike 1 , 2 lacks the C4-methyl group in unit F, which simplifies chemical synthesis greatly, albeit at a cost of biological relevance, since 2 is less active than 1 (as discussed later in this review). A number of EF disaccharide analogs ( 15-18 , 21-23 ) were prepared using different strategies 64-69 Scheme 1. shows one such route, which led to 16 .…”
Section: Moenomycins As a Target Of Chemical Synthesis And Degradatmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike 1 , 2 lacks the C4-methyl group in unit F, which simplifies chemical synthesis greatly, albeit at a cost of biological relevance, since 2 is less active than 1 (as discussed later in this review). A number of EF disaccharide analogs ( 15-18 , 21-23 ) were prepared using different strategies 64-69 Scheme 1. shows one such route, which led to 16 .…”
Section: Moenomycins As a Target Of Chemical Synthesis And Degradatmentioning
confidence: 99%
“…A number of EF disaccharide analogs (15)(16)(17)(18)(21)(22)(23) were prepared using different strategies. [64][65][66][67][68][69] Scheme 1 shows one such route, which led to 16. The route features relatively mild glycosylation conditions and an efficient solution to introduce the carbamate into unit F. The resultant disaccharides differ mainly in the structure of the lipid chain and substituents at the C4 position of unit F (Fig.…”
Section: Di-and Trisaccharide Moenomycin Analogs Via Chemical Degrada...mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of disaccharide analogues of moenomycin A have been shown to inhibit the transglycosylase in in vitro experiments but lack antibiotic activity. , From all available experimental evidence it can be concluded that antibiotically active moenomycin analogues must contain at least three carbohydrate units (C, E, and F; see formula 141 , Scheme ). Therefore, only the synthesis of trisaccharide analogues will be described here, and the synthetic work on disaccharide ,, and monosaccharide ,,,,, as well that on C -glycoside analogues will be omitted although especially the disaccharide analogues may be interesting compounds for exploring the acceptor binding site of the transglycosylase. A combinatorial approach to disaccharide analogues will, however, be included because of its methodic value.…”
Section: 4 Moenomycin Trisaccharide Analoguesmentioning
confidence: 99%
“…Acetylation of 229a yielded 229b , from which the anomeric acetyl group was selectively removed with hydrazinium acetate in DMF , to give 229c . The conversion into analogue 229c was achieved combining 229 and methyl 2-decyloxy-3-hydroxypropionate and methyl 2-[1,1‘-biphenyl]-3-ylmethoxy-3-hydroxypropionate via the phosphoric acid diester bridge using the phosphite approach as described above. ,,
40 Nicolaou's Coleophomone D Synthesis
…”
Section: 4 Moenomycin Trisaccharide Analoguesmentioning
confidence: 99%